Merdeka Belajar in Islamic Religious Education Learning (Case Study of Implementing the Merdeka Belajar Curriculum at SMP Negeri 1 Ngantru Tulungagung) - Rohmah, Liatul; Saerozi, Imam (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research analyzes “Merdeka Belajar” in Islamic religious education learning in implementing “Kurikulum Merdeka Belajar” at SMP Negeri 1 Ngantru Tulungagung. The research method used is a qualitative research approach. Data collection techniques are used to explore data by conducting interviews, observations, interviews, and documentation. The results of his research were that planning the “Kurikulum Merdeka” for Islamic Education Subjects at SMP Negeri 1 Ngantru Tulungangung was carried out using assessment planning in stages, including cognitive and non-cognitive diagnostic assessments, process assessments in the form of trigger questions and summative assessments. Implementation of the “Kurikulum Merdeka” for Islamic Education Subjects at SMP Negeri 1 Ngantru Tulungangung is done by implementing assessments before and after learning. In practice, if educators want to know students' cognitive abilities, educators present questions that are related to the learning material. Implementing the Merdeka Belajar curriculum starts with preliminary, core, and closing activities. Obstacles to implementing the “Kurikulum Merdeka” include limited material in student books, limited facilities and infrastructure, material in the Merdeka curriculum not yet fully mastered by teachers, implementation of an inclusive school system, limited technology capabilities that support the implementation of the “Kurikulum Merdeka.”